Dynamism and B2B firm performance: The dark and bright contingent role of B2B relationships - Chung, H.F.L.; Kingshott, Russel; MacDonald, R.V.G.; Putranta, M.P. (ELSEVIER SCIENCE INC, 2021)
Grounded by the contingency theory, we postulate a match and mismatch conceptualization that can be used to highlight the dark and bright side of business-to-business (B2B) relationships in the environmental dynamism-performance framework. The research conceptualization is examined using the survey data from 180 B2B firms operating in New Zealand. In this study, the mismatch of dynamism, B2B relationships and strategic performance, and a match of dynamism, B2B relationships and financial performance are both confirmed. Our study expands existing dark side relationship research by revealing that B2B relationships negatively moderate the effect of dynamism on B2B firms’ strategic performance. Our study also offers new insights by confirming the positive integrative effect of B2B relationships and dynamism on financial performance. Our findings significantly broaden contingency theory, environment, B2B relationships and performance research.